THE USE OF FLASHCARD TO IMPROVE THE MATERY OF ENGLISH CONCRETE NOUNS OF YOUNG LEARNERS - S.Thoriqul Huda Thoriq; Devi Dwi Kurniawan (Wiralodra English Journal, 2021)
Abstract The students in elementary schools level have many shortcomings in memorizing vocabulary so that they tend to have lack of vocabulary. One of the factors that can affect the students with lack of vocabulary is using teaching media. Flashcards as teaching media can be used to enrich the students’ vocabulary. In this research, the purpose is to improve the students’ vocabulary using flashcards to the First Grade of SDN Sambong 3 Batang. Based on the writer’s experiences during teaching, the students were having lack of vocabulary. Therefore, this research is expected to find a solution to the students’ problem in mastering vocabulary. The method used in this research is a Classroom Action Research which consisted of Planning, Acting, Observing, and Reflecting. This method was done in two cycles in order to get better result of the research. The subject of the study is the first Grade of SDN Sambong 3 Batang. The total number of research participants was 22 students. The technique used for collecting data was using by observation. The findings of this research were that the students’ progress during teaching and learning activity in classroom that the students did the discussion group and presented the result of the group discussion in front of the class. The students did the assessment in the form of multiple choices after having the discussion. Keywords: Learning Vocabularies , Flashcard Technique